Strategi Tindak Tutur Langsung dan Tidak Langsung Pedagang dalam Menerima dan Menolak Pembeli Di Pasar Aur Kuning Bukittinggi - Tressyalina Tressyalina; Haniya annisa (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2020)
The interaction between traders and buyers using language as a communication tool is called speech act. This study aims to describe the direct and indirect speech acts that occur between traders in accepting and rejecting buyers in the Aur Kuning Bukittinggi market. To obtain data the author uses the method of referencing and note-taking techniques. After the data is collected, speech act theory is used to analyze the data. In this research, work steps include reduction, presentation of data, and drawing conclusions. Based on the results of the study, it can be concluded that the speech acts used in the sale and purchase contraction between traders and buyers in the Bukittinggi aur yellow market, namely the speech act directly accepts buyers belonging to thevivial function, the speech act strategy rejects the buyer classified into the collaborative function. Indirect speech acts accept buyers classified into thevivial function, indirect speech strategies reject buyers classified into collaborative functions.